Bi-fluorescent Staphylococcus aureus infection enables single-cell analysis of intracellular killing in vivo - Hinman, Kristina D.; Laforce-Nesbitt, Sonia S.; Cohen, Joshua T.; Mundy, Miles; Bliss, Joseph M.; Horswill, Alexander R.; Lefort, Craig T. (Frontiers in Immunology, 2023)
Techniques for studying the clearance of bacterial infections are critical for advances in understanding disease states, immune cell effector functions, and novel antimicrobial therapeutics. Intracellular killing of Staphylococcus aureus by neutrophils can be monitored using a S. aureus strain stably expressing GFP, a fluorophore that is quenched when exposed to the reactive oxygen species (ROS) present in the phagolysosome. Here, we expand upon this method by developing a bi-fluorescent S. aureus killing assay for use in vivo. Conjugating S. aureus with a stable secondary fluorescent marker enables the separation of infected cell samples into three populations: cells that have not engaged in phagocytosis, cells that have engulfed and killed S. aureus, and cells that have viable internalized S. aureus. We identified ATTO647N-NHS Ester as a favorable dye conjugate for generating bi-fluorescent S. aureus due to its stability over time and invariant signal within the neutrophil phagolysosome. To resolve the in vivo utility of ATTO647N/GFP bi-fluorescent S. aureus, we evaluated neutrophil function in a murine model of chronic granulomatous disease (CGD) known to have impaired clearance of S. aureus infection. Analysis of bronchoalveolar lavage (BAL) from animals subjected to pulmonary infection with bi-fluorescent S. aureus demonstrated differences in neutrophil antimicrobial function consistent with the established phenotype of CGD.